Tragedia lalki w żywiole komedii. Operowy kontekst filmu Aria Piotra Sapiegina (2001) - Igielska, Anna (Res Facta Nova, 2018)
The subject of the analysis is the animated puppet film Aria by Pjotr Sapegin, which refers to the plot and the music – through the quotes from the aria ‘Un bel dì vedremo’ in the arrangement of Normand Roger – of the opera Madama Butterfly by Giacomo Puccini. By taking as a main reference point a description of musical operations made in the film and their contribution in constructing the meanings of the audiovisual work, the author of the article moves successively between several interpretation levels: historical (she situates the film within the puppet’s opera tradition), media-theoretical (she considers the qualitative transformation of the doll in theater and film in the perspective of different aesthetics of both media), theatrological (she reflects on the doll’s ontology, with particular emphasis on the question of comicality), and operological (she refers in part to the entire opera of Puccini and portrays more accurately verbal, musical and dramaturgical values of the aria ‘Un bel dì vedremo’, while proving that the Sapegin’s film is an example of meta-reflection on aria as a form of dramatic-musical expression). The multiple perspectives of the study are used to reveal the dramatic, stylistic, adaptive and philosophical complexity of Sapegin’s work and lead to the recognition of the capabilities of an animated film as an audiovisual medium that continually leads a creative dialogue with music as well as the potential of the puppet aesthetics at the beginning of the 21st century.